Технология изготовления контрольных образцов из неметаллов для капиллярной дефектоскопии; Дефектоскопия; № 11 - Калиниченко Н. П. Николай Петрович; Калиниченко А. Н. Алексей Николаевич; Лобанова И. С. Ирина Сергеевна; Борисов С. С. Станислав Сергеевич (2013, 2013)
Заглавие с экрана